Effects of natural dissolved organic matter on the complexation and biodegradation of 17α-ethinylestradiol in freshwater lakes. (March 2019) - Bai, Leilei; Zhang, Qi; Wang, Changhui; Yao, Xiaolong; Zhang, Hui; Jiang, Helong
Abstract: Natural dissolved organic matter (DOM) produced in algal blooms and overgrowths of macrophyte changes the elimination and ecotoxicity of estrogens in freshwater lakes. The complexation of 17α-ethinylestradiol (EE2) and various DOMs, including the water- and sediment-derived DOMs from the algal-dominant zone in Lake Taihu (TW and TS, respectively) and the macrophyte-dominant zone in Poyang Lake (PW and PS, respectively), and the humic acid (HA), was investigated along with the subsequent effects on EE2 biodegradation. Dialysis equilibrium experiments showed that binding to DOM significantly decreased the freely soluble concentrations of EE2. The binding capacity of the five DOMs followed the order of PW < TW < PS ≈ TS < HA. A negative correlation was found between the organic-carbon-normalized sorption coefficient (log K DOC ) and the absorption ratio (E2 /E3 ) of DOM, indicating that the large sized, aromatic molecules were involved in the complexation. The reduced freely soluble concentrations of EE2 did not inhibit its biodegradation by an EE2-degrading strain, Rhodobacter blasticus . Conversely, the autochthonous-dominated water-derived DOMs stimulated a more extensive biodegradation of EE2 than the sediment-derived DOMs, and the existence of HA resulted in the smallest increase in EE2 biodegradation. The promoting effect was associated with the increased concentration, activity, and transforming rate of R. blasticus by the bioavailable components in DOM. The present study suggests that the significant impact of natural DOM should be fully considered when assessing the fate and ecological risks of estrogens in eutrophic waters. Graphical abstract: Image 1 Highlights: Complexation of DOM and EE2 was quantitatively studied using dialysis equilibrium. The affinity for EE2 was positively correlated with the molecular weight of DOM. Complexation of DOM did not significantly decrease the bioavailability of EE2. Autochthonous-dominated DOM exhibited a strong promotion on EE2 biodegradation. Abstract : Complexation of natural dissolved organic matter promoted the biodegradation of EE2.